Physical fitness and balance performance in table tennis players with intellectual disabilities - Gimunová, Marta; Akbulut, Ahmet Batuhan; Bozděch, Michal; Válková, Hana; Paludo, Ana Carolina (University of Ljubljana, 2024)
Training routine is beneficial for people with intellectual disabilities, increasing their physical fitness, improving the balance and consequently reducing the risk of falls. However, during the COVID-19 breakdown, training restrictions could impair these benefits. This is a two-fold study aimed to compare the physical fitness performance and balance in tennis table athletes with intellectual disability (ID) during 2016 and 2022; and to analyse the association between the fitness and balance parameters. Table tennis athletes with ID, from both sexes and members of the Special Olympics Czech Republic, were assessed in 2016 (n=33) or 2022 (n=32). The FunFitness protocol was used to measure the physical fitness parameters and balance (e.g., functional shoulder rotation, timed sit-to-stand test, partial sit-up test, handgrip test, single leg stance eyes open, single leg stance eyes closed). Comparison and correlation statistical tests were used (p<0.05). The physical fitness parameters and balance presented no statistically significant change or better results in the year 2022 suggesting that despite the restrictive measures related to Covid-19, no statistically significant deterioration in fitness was observed in the year 2022 compared to pre-pandemic testing. Correlation of physical fitness parameters and balance demonstrated that balance is positively related with flexibility and lower limb strength. Future studies focused on the relationship between flexibility and balance in different sport modalities would bring a better insight into the role of flexibility on balance in population with ID.